Adenosine A(1), A(2a), A(2b), and A(3) receptors in hematopoiesis. 1. Expression of receptor mRNA in four mouse hematopoietic precursor cells - Štreitová, D; Sefc, L; Savvulidi, F; Pospíšil, M; Holá, J; Hofer, M (Physiological research, 2010)
Four mouse bone marrow or thymus cell populations, namely granulopoietic/monocytopoietic, erythropoietic, B-lymphopoietic, and T-lymphopoietic precursor cells have been assayed by RT-PCR technique for the presence and relative amounts of adenosine A(1), A(2a), A(2b), and A(3) receptor mRNA. It has been found that (i) all four populations studied express all four adenosine receptor subtypes, (ii) the A(1), receptor is the least expressed in all populations studied, (iii) the A(3) receptor is markedly expressed in the populations of granulopoietic/monocytopoietic and erythropoietic cells, (iv) the A(2a) receptor is markedly expressed in the populations of B-lymphopoietic and T-lymphopoietic cells, and v) the A(2b) receptor does not predominate in any of the precursor cells studied. Our data offer a new possibility for the assessment of the readiness of these cells to respond, by receptor-mediated mechanisms, to adenosine or its analogs present in the tissues as a result of endogenous processes and/or following their administration.
Keywords: Receptor, Adenosine A3; Gene Expression Regulation; RNA, Messenger; Hematopoiesis; purinergní receptory P1; polymerázová řetězová reakce; receptor adenosinový A3; separace buněk; Receptor, Adenosine A1; Receptor, Adenosine A2A; hematopoetické kmenové buňky; Animals; ženské pohlaví; Cell Separation; zvířata; regulace genové exprese; hematopoéza; myši inbrední C57BL; receptor adenosinový A2A; Receptor, Adenosine A2B; myši; Mice, Inbred C57BL; receptor adenosinový A1; Polymerase Chain Reaction; Hematopoietic Stem Cells; receptor adenosinový A2B; Mice; Female; messenger RNA; Receptors, Purinergic P1